Shifting Religious Identity Pedagogy at the Wahid Hasyim Islamic Boarding School Yogyakarta - Kholik, Nur (At-Tajdid: Jurnal Ilmu Tarbiyah, 2024)
This study explores the shift in identity and pedagogical authority of Islam at Wahid Hasyim Islamic Boarding School in Yogyakarta. This shift reflects the pesantren's adaptation to global challenges by integrating modern scientific knowledge into its tradition of education rooted in Islamic values. The study examines how Islamic knowledge and pedagogy are constructed in the pesantren and how the shift in identity and pedagogical authority impacts the formation of students' religious identity. Utilizing observation, interviews, and documentation methods, the research highlights the integration of Salafi and Kulliyah curricula, innovations in teaching methods, and adaptation of human resources. The findings indicate that this shift creates a contextual and relevant model of Islamic education, where tradition-based pedagogy, particularly memorization, not only serves as a medium for knowledge transmission but also as a tool for shaping students' religious identity holistically, linking spiritual values with modern challenges.